Safe Gynecological Laparoscopic Surgery during COVID Times - Prakash Harikant Trivedi; Soumil Prakash Trivedi; Nilesh Maruti Ghadge; Dinesh Popatlal Bajani; Aditi Soumil Trivedi (Wolters Kluwer Medknow Publications, 2020)
Background: SARS-CoV-2 virus is largely transmitted via respiratory droplets and the highest transmission risks arise when undertaking aerosol generating procedures like laparoscopy. Most national societies had advised the urgent suspension of elective surgery with the focus shifting to emergency and cancer surgery only during this pandemic. However very little is known regarding the risks to the health care professionals undertaking emergency laparoscopic procedures. Aims and Objective: To demonstrate safety at laparoscopy by modifying the technique for safe management of patients during the COVID-19 pandemic. Design and Setting: This is an observational cohort study. This study was done at a tertiary care reference hospital for minimal access gynaecological surgery. Safety of 42 semi-urgent and emergency laparoscopic surgeries in patients was evaluated for a period of 5 months after taking informed written consent of patients to participate in the study. Materials and Methods: Use of double closed circuit laparoscopic suction evacuation and filtration systems with closed circuit anaesthesia with specialized Heat and Moisture Exchangers (HME) bacterial & viral (BV) filters to make laparoscopic surgery safe. Results: 57.14% of the patients were 41 years or more. 47.6% presented either with menorrhagia, irregular vaginal bleeding or post-menopausal vaginal bleeding and 26.19 % patients were keen to conceive. In 50% patients, surgery was done in 60 minutes or less. Post-operatively, none of the patients had any complications and all were followed up for 14 days for COVID-19 infection. No staff, doctors or anaesthetist were detected COVID-19 positive during the follow up period. The limitation of the study was, that it was an observational study done in COVID-19 negative patients only. Conclusions: Safety at laparoscopy can be maintained when it is performed by an experienced surgeon who has full knowledge of safe laparoscopic techniques and performs it in the shortest time possible and with all due precautions.